Oman Entrepreneurship Highlights: A Case Study of Nawa International - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2019)
Entrepreneurship in Oman is still relatively on the premature stage of development considering the current conditions within the Omanis business policies and structure that hinders the full potential of the SME sector in the country. Amidst the challenging SME business environment in Oman is a thriving company proving that there is room for growth for entrepreneurs in the country. The discussion will highlight Nawa International and its key entrepreneurial leader and Managing Director Mr. Khalid Al Suleimany in terms of analyzing how the company’s entrepreneur and their outlook enabled the organization’s growth. Both the challenges and achievements will be highlighted in the discussion with analysis done on the factors affecting the success or failure of the SMEs in the country. In here, the business overview will provide relevant insights regarding the company followed by a discussion on the key characteristics that the organization’s entrepreneur have that enables positive output. Furthermore, the discussion will also highlight assumption about the business and the SME sector in Oman as a whole, which also includes discussion on the key issue and analysis of the described factors that drives the failure and success of the SME businesses in the country including that of Nawa International.